RETRACTED: The Effect of Treatment Temperature on Microstructure and Mechanical Behavior of a Fine-Grained YSZ–NiO(Ni) Anode Material - Bogdan Vasyliv; Volodymyr Kulyk; Zoia Duriagina; Taras Kovbasiuk (Crystals)
Reduction–oxidation (redox) cycling of a solid oxide fuel cell (SOFC) due to leakage of a fuel or standby and shutdown cycling is an issue that has attracted the attention of many research groups for a long time. The researchers mainly note the harmful effects of redox cycling on the microstructure of SOFC constituents and search for ways to mitigate or diminish them. The purpose of this study was to use reduction and oxidation stages in an appropriate mode as a positive preconditioning to improve redox cycling stability of Ni-containing SOFC anode materials. The redox treatment was applied to YSZ–NiO(Ni) anode substrate specimens at 600 °C and 800 °C. The mechanical tests (flexural strength, microhardness, and fracture toughness) were performed on these specimens and the results were compared to those for as-sintered and one-time reduced specimens. Microstructure and fracture surface morphology of material in corresponding modes were analyzed. The main findings were summarized as follows: (i) Redox treatment at 600 °C provides an increase in flexural strength and electrical conductivity of YSZ–NiO(Ni) anode cermets; (ii) the treatment at 800 °C causes formation of a gradient microstructure with lateral cracks that result in a significant decrease in flexural strength; (iii) the mode of redox treatment at 600 °C for 4 h in Ar–5% H2/air atmosphere provides an increase in flexural strength of YSZ–NiO(Ni) anode cermets (up to 127 ± 4 MPa), while electrical conductivity was provided at a comparatively high level (7 × 105 S/m).